Pengaruh penambahan betain dalam pakan rendah metionin terhadap kualitas karkas itik Mojosari jantan (Faculty of Animal Science, Universitas Brawijaya, 2015)
The objective of this research was to observe the effect of betaine in feed to carcass, breast meat, thigh meat, abdominal fat, and meat cholesterol in Mojosari male ducks. The materials of this experiment were 144 male ducks which were maintained for 8 weeks. P0 was control treatment with no betaine were added, whereas P1 0.1%, P2 0.2%, P3 0.3% of betaine addition in the feed. The method used in this research was field experiments with 4 treatments and 6 replications. The parameters that measured in this research were carcass percentage, percentage of breast and thigh meat, abdominal fat, and breast cholesterol. Data were tabulated into MS. Excel and analyzed using ANOVA of Completely Randomized Design (CRD). If there were significant differences among the treatments, it will be tested by Duncan’s Multiple Range Test. The result showed that addition of betaine had a significant effect (P<0.05) on carcass percentage, percentage of breast and thigh meat, but it didn’t has a significant effect (P>0.05) on cholesterol of breast meat and abdominal fat. The use of betaine in low methionine feed could improve carcass percentage, percentage of breast and thigh meat deposition, and lower abdominal fat percentage, but it has no effect on the cholesterol content of breast meat in Mojosari male ducks. The research concluded that 0.3% of betaine administration on feed was the best result for Mojosari male duck carcass quality, in terms of carcass percentage, the percentage of breast meat and thigh, and lower abdominal fat percentage. Keywords : Betaine, addition, low metionin, carcass, Mojosari duck